1991
DOI: 10.1159/000173391
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Glucose Decarboxylation in the Substrate-Limited Isolated Perfused Kidney

Abstract: Rat kidneys were perfused with a cell-free perfusate containing substrate-free albumin, different glucose concentrations (0.20–5.0 mmol/l), and uniformly labeled 14C-glucose. The rate of glucose decarboxylation (Qox), as a function of [glucose]p, displayed saturation kinetics [Vmax = 0.35 µmol/(g · min); Km = 0.87mmol/l]; saturation occurred at [glucose]p = 1.0–2.0mmol/l. Although the presence of as low as 0.2mmol/l of glucose significantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This glucose production probably masks, at the whole-organ level in vivo, the concurrent utilization of glucose by the distal segments of the nephron. Several authors have demonstrated that glucose can be metabolized by various preparations of the rat kidney (Underwood & Newsholme, 1967;Weidemann & Krebs, 1969;Hems & Gaja, 1972;Ross et al 1973;Anaizi & Cohen, 1991). Although Elhamri et al (1993) could not demonstrate a statistically significant change in renal glucose handling during starvation, there was a tendency for glucose removal to decrease in their study.…”
Section: Adaptative Changes In Fuel Selection By the Rat Kidney Durinmentioning
confidence: 86%
See 1 more Smart Citation
“…This glucose production probably masks, at the whole-organ level in vivo, the concurrent utilization of glucose by the distal segments of the nephron. Several authors have demonstrated that glucose can be metabolized by various preparations of the rat kidney (Underwood & Newsholme, 1967;Weidemann & Krebs, 1969;Hems & Gaja, 1972;Ross et al 1973;Anaizi & Cohen, 1991). Although Elhamri et al (1993) could not demonstrate a statistically significant change in renal glucose handling during starvation, there was a tendency for glucose removal to decrease in their study.…”
Section: Adaptative Changes In Fuel Selection By the Rat Kidney Durinmentioning
confidence: 86%
“…The rates of substrate uptake or metabolite release measured are only net rates and do not take into account the possibility that synthesis and degradation of a given substrate occur simultaneously. Indeed, it is well established that whole rat kidney has the capacity to utilize glucose via glycolysis (Hems & Gaja, 1972;Cohen et al 1977;Anaizi & Cohen, 1991) and synthesize glucose via gluconeogenesis (Nishiitsuji et al 1967;Bowman, 1970;Hems & Gaja, 1972). Similarly, whole rat kidney can form lactate by glycolysis under aerobic or anaerobic conditions (Hems & Gaja, 1972;Bartlett et al 1984) and utilize lactate as a substrate (Nishiitsutji ef al.…”
Section: S U B S T R a T E U T I L I Z A T I O N A T T H E W H O L E mentioning
confidence: 99%